2003
DOI: 10.1055/s-2003-37701
|View full text |Cite
|
Sign up to set email alerts
|

Jatrophane Diterpenes from the Latex ofEuphorbia obtusifoliawith Inhibitory Activity on the Mammalian Mitochondrial Respiratory Chain

Abstract: Seven diterpenes isolated of the latex of the Euphorbia obtusifolia were evaluated as inhibitors of the NADH oxidase activity in submitochondrial particles from bovine heart. Compound 2, 2,3,5,7,8,9,15-heptahydroxyjatropha-6(17),11-diene-14-one 8,9-diacetate 7-isobutyrate 2,3-bis(2-methylbutyrate), was the most potent inhibitor with an inhibitory concentration (IC 50 ) value of 5.1 +/- 0.2 microM. In the present study, some structure-activity trends are suggested for the inhibitory activity of these natural pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…9 It was found that the euphocharacins 3j and 3k (Figure 2) are stronger inhibitors of the cellular P-glycoprotein-mediated daunomycin efflux than cyclosporine A, a compound which was advanced to clinical trials as a multidrug-resistance reversal agent. 10 A variety of different biological activities have been reported for jatrophane diterpenes: inhibitory activity on the mammalian mitochondrial respiratory chain, 11 cell cleavage arrest, 12 cytotoxicity against various human cancer cell lines, 13 antiviral activity, 14 antiplasmodial activity, 15 microtubule interaction, 16 multidrug resistance modulating activity, 17 and inhibition of the P-glycoprotein. 18 These findings coupled with intriguing structure of the densely functionalized bicyclic jatrophane core have prompted synthetic efforts by the groups of Mulzer 19 and Uemura, 20 as well as our group.…”
Section: Introductionmentioning
confidence: 99%
“…9 It was found that the euphocharacins 3j and 3k (Figure 2) are stronger inhibitors of the cellular P-glycoprotein-mediated daunomycin efflux than cyclosporine A, a compound which was advanced to clinical trials as a multidrug-resistance reversal agent. 10 A variety of different biological activities have been reported for jatrophane diterpenes: inhibitory activity on the mammalian mitochondrial respiratory chain, 11 cell cleavage arrest, 12 cytotoxicity against various human cancer cell lines, 13 antiviral activity, 14 antiplasmodial activity, 15 microtubule interaction, 16 multidrug resistance modulating activity, 17 and inhibition of the P-glycoprotein. 18 These findings coupled with intriguing structure of the densely functionalized bicyclic jatrophane core have prompted synthetic efforts by the groups of Mulzer 19 and Uemura, 20 as well as our group.…”
Section: Introductionmentioning
confidence: 99%
“…In this study a set of forty natural compounds, including: flavonoids, flavonols, chalcones, diterpenes, isoflavones, and catechin, acting as NADH-oxidase inhibitors ( Table 1 ), were selected from refs [ 1 , 2 , 3 , 4 , 5 ]. Biological activities were measured as the concentration required for 50% inhibition of NAOH-oxidase from beef heart [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Natural products provide opportunities in drug discovery, leading to a detailed understanding of biological pathways and revealing the functions of involved enzymes or receptors. The inhibition of NADH-oxidase and others mitochondrial enzyme systems may be an underlying mechanism for cytotoxicity and other biological effects of natural products [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, jatrophanes are potent and specific P‐glycoprotein modulators . In addition, a variety of other biological activities have been reported: inhibitory activity on the mammalian mitochondrial respiratory chain, antiviral activity, microtubole interaction, antiplasmodial activity, and cytotoxicity against various human cancer cell lines…”
Section: Figurementioning
confidence: 99%